The influence of new scientific information on the treatment of elderly patients in general practice - Kubesová, H; Holik, J; Bogrova, I (Acta medica Austriaca, 2001)
UNLABELLED: It has been proven that with an increasing number of diseases elderly patients are treated by an increasing number of drugs despite the fact that treatment of elderly persons should be as simple as possible. Simpler dosage of (fewer?) drugs may contribute to a good cooperation on the part of patients, as well as to a lower incidence of undesirable effects and drug interactions. Sticking to established medication schemes is another feature observed in practice, which interferes with the introduction of novelties. The aim of this study was to investigate the actual situation of medication of elderly patients treated by general practitioners in this country. Between 1996 and 1998, a random group of 1481 patients aged older than 75 was studied in cooperation with general practitioners. A detailed history was obtained and physical examination was performed, signs of depression were assessed, Barthel's test of everyday activities, and IADL (activities of daily living) and MMSE (Mini Mental State Examination) tests were applied. A unified "Protocol on Examination" was used in which three questions were concerned with medication--the kinds of drugs taken by the patient, their names and dosage, and whether any hypnotics were taken. The five most frequently prescribed groups include vasodilators (62% patients), cardiotonics (39%), analgetics (41%) and Ca-antagonists (25%). The dynamics of the prescription were remarkable--a significant decrease of the use of analgetics and cardiotonics was observed in comparison with a significant increase in the use of ACE inhibitors. The number of drugs administered is as follows: while only 1.3% patients took no drugs, 1.6% patients took more than 13 drugs. 61% patients rank among the categories taking 4-5 or 6-8 kinds of drugs. On the whole, general practitioners tend to prescribe medicaments in doses one tablet per day. CONCLUSIONS: The results suggest that, even nowadays, elderly patients are treated with a rather high number of medicaments. In contrast, the dosage of one tablet a day decreases the total number of the tablets taken. A significant influence of new scientific information was visible in the prescription habits of general practitioners. Be that as it may, in elderly patients, the simplest possible medication should continue to be aimed at.
Keywords: senioři; farmakoterapie; činnosti denního života; senioři nad 80 let; Geriatrics; anamnéza; Česká republika; Mental Status Schedule; geriatrie; Activities of Daily Living; Czech Republic; Family Practice; Aged, 80 and over; Drug Therapy; Humans; Medical History Taking; záznam o duševním stavu; rodinné lékařství; Aged; lidé